1999
DOI: 10.3171/jns.1999.90.2.0265
|View full text |Cite
|
Sign up to set email alerts
|

Benign cerebellar astrocytomas in children

Abstract: The presence of brainstem involvement (tumor in the transitional form) emerged as a significant negative prognostic factor and should be treated as a distinct nosological entity. The extent of surgical excision has a significant bearing on the risk of tumor recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
110
3
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 61 publications
5
110
3
3
Order By: Relevance
“…Improvement in imaging and surgical techniques has resulted in improved morbidity and mortality rates. Most authors agree that complete surgical resection of the tumor is an important prognostic factor on tumor recurrence and survival rates (1,8,13,16,18). Gjerris et al (9) report a survival rate of 94% and Zakrzewski et al (23) report 88% for 25-year survival.…”
Section: Bilginer B Et Al: Cerebellar Pilocytic Astrocytomas In Chilmentioning
confidence: 98%
See 1 more Smart Citation
“…Improvement in imaging and surgical techniques has resulted in improved morbidity and mortality rates. Most authors agree that complete surgical resection of the tumor is an important prognostic factor on tumor recurrence and survival rates (1,8,13,16,18). Gjerris et al (9) report a survival rate of 94% and Zakrzewski et al (23) report 88% for 25-year survival.…”
Section: Bilginer B Et Al: Cerebellar Pilocytic Astrocytomas In Chilmentioning
confidence: 98%
“…Sgouros et al (20) reported that the outcome in cystic tumors is not so much different between total and subtotal resections. Pencalet et al (16) reported that they remove any macroscopically apparent abnormal cyst wall because of the risk of recurrence. In our series, gross total resection was performed for all cystic tumors and we resected the cyst wall if contrast enhancement had been observed in the preoperative MRI.…”
Section: Bilginer B Et Al: Cerebellar Pilocytic Astrocytomas In Chilmentioning
confidence: 99%
“…Malignant gliomas are quite uncommon in the childhood cerebellum. The median age at diagnosis is 5 to 6 years, with 20% of cases younger than 3 years; astrocytomas of this location are rarely found in infants (206,207). Presenting symptoms often are confined to those associated with elevated intracranial pressure, with less frequent altered cerebellar function; cranial nerve deficits are uncommon.…”
Section: Cerebellar Astrocytomasmentioning
confidence: 99%
“…The classic cystic CA presents as a unilocular cyst with a single prominent mural nodule. The cerebellum is one of the most common sites of origin for LGA in children, JPAs comprise 80% to 95% of cases and DFA account for 5% to 15% (206). DFAs tend to be less circumscribed, more infiltrative and expansile, with a less favorable prognosis relative to JPA; the diffuse tumors arise specified, or as oligoastrocytomas.…”
Section: Cerebellar Astrocytomasmentioning
confidence: 99%
“…As most pediatric brain tumors they commonly present with symptoms of increased intracranial pressure or parenchymal compression, including failure to thrive (lack of appropriate weight gain), developmental delay, impaired consciousness, nausea, vomiting, irritability, headache, etc. In case of a cerebellar tumor location, gait abnormalities, ataxia, dysmetria and nystagmus belong to the common clinical signs (Gol et al, 1959;Pencalet et al, 1999). Chiasmatic-hypothalamic PAs typically lead to visual loss or visualfield deficit, hypothalamic-pituitary dysfunction, as well as symptoms secondary to hydrocephalus (Burger et al, 2000b).…”
Section: Pilocytic Astrocytomamentioning
confidence: 99%